E-GOVERNMENT SISTEM ADMINISTRASI KEPENDUDUKAN BERBASIS WEB PADA DESA JAWISARI KECAMATAN LIMBANGAN KABUPATEN KENDAL - SATRIA PRAKOSO, DICKY; TRI HANDOKO, DRS.,M.KOM, WIDIYANTO (Information Technology and Telematics, 2018)
Abstract- Problems that occur in Jawisari Village Limbangan subdistrict required the system of population administration. Population system to be developed must support the service to the community, one of the media used is the information technology media to form an electronic government (e-government) concept that contains the population administration system. The benefits of e-government implementation in each layer is to improve the function of public services and improve the performance of human resources and directly improve the efficiency and effectiveness of Jawisari Kecamatan Limbangan. System development method used in this research is Waterfall, system design using UML and system implementation using PHP and MySQL. The result of this research is E-Government web-based population administration system at Jawisari Village District Limbangan Kendal District can be used for introduction of identity card making, making of family card, birth, arrival, moving, death and IMB Keywords – E-Government, Jawisari Village District Limbangan, PHP, MySQL DAFTAR PUSTAKA Aditya, A.N, (2010) Jago PHP & MySQL Dalam Hitungan Menit, Dunia Komputer, Bekasi Amalia, E., Supriatna, Y.,  (2017) Perancangan Sistem Informasi Administrasi Kependudukan Sebagai Pengembangan E-Government, Skripsi, Universitas Widyatama Ariyoso, D., Manurung, L.,  (2013) Penerapan E-Government Dalam Pelayanan Elektronik Akta Kelahiran (E-Akta) Pada Suku Dinas Kependudukan Dan Pencatatan Sipil Kota Administrasi Jakarta Pusat, Skripsi, Universitas Indonesia Dharwiyanti, S., Wahono, R.S., (2003), Pengantar Unified Modeling Language (UML), http://www.unej.ac.id/pdf/yanti-uml.pdf diakses pada tanggal 22/03/2017 Handayaningrat, S., (2002) Pengantar Studi Ilmu Administrasi dan Manajemen, Haji Masagung, Jakarta Indrajit, R. E., (2005) E-Government Strategi Pembangunan Dan Pengembangan Sistem Pelayanan  Publik Berbasis Teknologi Digital. Andi Offset, Yogyakarta Junaidi,  (2013) Implementasi Electronic Government Untuk Penyelenggaraan Pelayanan Administrasi Kependudukan, Skripsi, Universitas Brawijaya Prasetyo, D.D, (2006), Administrasi Database Server MySQL, Elex Media Komputindo, Jakarta Presiden Republik Indonesia., (2008), Persyaratan Dan Tata Cara Pendaftaran Penduduk  Dan Pencatatan Sipil, PP No 25 Tahun 2008 Supriyanto, A, (2005) Pengantar Teknologi Informasi, Salemba Infotek, Jakarta Undang-Undang Nomor 24 Tahun 2013, (2013) Perubahan Undang-Undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan (Lembaran Negara Republik Indonesia Tahun 2013 Nomor 232, Tambahan Lembaran Negara Nomor 5475).  UU No.24 Tahun 2013 Whitten, J.L. (2004) Metode Desain dan Analisa Sistem, Andi Offset, Yogyakarta